2007
DOI: 10.1016/j.rmed.2006.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Flow and volume responses after routine salbutamol reversibility testing in mild to very severe COPD

Abstract: Our hypothesis that COPD patients on the mild side of the severity spectrum differ from patients on the severe side regarding the association between their bronchodilator flow and volume responses was confirmed. The difference is probably explained by the higher degree of loss of lung elastic recoil and/or compression of the smaller airways due to enlarged air spaces that accompanies the progression of COPD to the more severe stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 23 publications
5
49
0
1
Order By: Relevance
“…(4) In recent years, some studies have demonstrated that, in COPD patients, increases in vital capacity and inspiratory capacity reflect reduced residual volume, which correlates with decreased dyspnea and improved exercise performance, even in the absence of improved FEV 1 . (5,6) Therefore, the variation in FEV 1 might not suffice as an indicator of reversibility in this particular case. (7) In fact, there is no consensus regarding the best technique to evaluate the effect of bronchodilator administration in COPD patients.…”
Section: Introductionmentioning
confidence: 95%
“…(4) In recent years, some studies have demonstrated that, in COPD patients, increases in vital capacity and inspiratory capacity reflect reduced residual volume, which correlates with decreased dyspnea and improved exercise performance, even in the absence of improved FEV 1 . (5,6) Therefore, the variation in FEV 1 might not suffice as an indicator of reversibility in this particular case. (7) In fact, there is no consensus regarding the best technique to evaluate the effect of bronchodilator administration in COPD patients.…”
Section: Introductionmentioning
confidence: 95%
“…The topic of whether the bronchodilator response in FEV 1 is limited in COPD patients has been discussed, 4 and studies have explored the reversibility of FEV 1 , forced vital capacity (FVC) and FEV 1 /FVC based on disease stage (based on GOLD stages). 5,6 Other studies suggest that the reversibility of FEV 1 is not a useful tool in COPD and that there might be many other relevant parameters when evaluating the response. 4 In some studies, other advanced lung function parameters are used to evaluate the response, [7][8][9][10][11][12][13] but there is no information about the clinically significant response and the parameters that are most effective to use.…”
Section: Introductionmentioning
confidence: 99%
“…About 50% of patients with COPD use long-acting bronchodilators, to achieve maximum airway dilatation [5]. Although these agents improve symptoms, recently doubt re-emerged concerning their safety, especially in terms of cardiovascular conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite smoking cessation programs, approximately 50% of COPD patients continue to smoke [5,15]. Although the effects of smoking and bronchodilators on mortality in COPD patients have been extensively studied, their interaction surprisingly has not.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation